Pluronic F127-Modified Electrospun Fibrous Meshes for Synergistic Combination Chemotherapy of Colon Cancer - Xie, Dengchao; Ma, Panpan; Ding, Xin; Yang, Xiao; Duan, Lian; Xiao, Bo; Yi, Shixiong (Frontiers in Bioengineering and Biotechnology, 2021)
Colon cancer ranks as the third most common malignancy in the world. Combination chemotherapy, resorting to electrospun fibrous technology, has been considered as a promising strategy to exert synergistic effects in colon cancer treatment. Herein, we manufactured various pluronic F127 (PF127)-modified electrospun fibrous meshes with different weight ratios of camptothecin (CPT) and curcumin (CUR). The fluorescence characterization of the obtained PF127-CPT-meshes, PF127-CUR-meshes, and PF127-CPT/CUR-meshes (2:1) showed that CPT and CUR were evenly distributed within individual fibers of these meshes. Drug release experiments revealed that both types of drugs could be released from fibrous meshes simultaneously and sustainably. Importantly, these meshes exhibited strong in vitro anti-colon cancer activities, compared with the control meshes without drugs. Moreover, the combination index values of the PF127-CPT/CUR-meshes (CPT/CUR weight ratio = 5:1, 3:1, or 2:1) were less than 0.5 after incubation for respective 24 and 36 h, indicating the synergistic anti-colon cancer effects of CPT and CUR in fibrous meshes. Collectively, these results demonstrate that PF127-CPT/CUR-meshes can be developed as an efficient implantable system for effective synergistic treatment of colon cancer.